Experimental tests on seismic retrofit of RC bridge piers - Pedro Delgado (2006)
The main purpose of this paper is to present an experimental campaign of different strategies for theseismic retrofit of reinforced concrete bridge piers and evaluating benefits concerning their structuralbehaviour under the cyclic loading.The setup of the RC pier experimental tests was specially designed to carry out bending with axial load,using a horizontal and a vertical actuator (with a slide device to allow top displacements of the pier). Asquare hollow section RC pier (450 mm x 450 mm, and 75 mm thick), similar to another one tested at thelaboratory of Pavia University in Italy, and a rectangular hollow section RC pier of 450 mm x 900 mm(with the same thickness) were tested at LESE - Laboratory of Earthquake and Structural Engineering atFaculty of Engineering of University of Porto.Besides numerical simulations of RC piers, which are not presented herein, the aim is to contribute fordeveloping and calibrating a procedure that enables the evaluation of the efficiency of the differentretrofit solutions, their possibilities and fields of application.